Consolidation in the luxury sector : study of a merger between LVMH and Hermès - Queiroz, Duarte Teixeira de Melo e Lacerda de (2012)
The current degree of globalization that characterizes most of the world’s modern markets has created a fertile ground for the advent of focused, multinational groups of companies. The complexity of these entities presents itself both as a remarkable achievement in sociological terms but also gives way to new and challenging aspects that human rationality must explore, counting on its inherent curiosity. In this context, this thesis makes an attempt to tackle the problem of valuing multinational firms and providing a possible outcome to a hypothesized merger between two global players in the luxury sector: LVMH and Hermès. The goal that this work proposes to achieve includes an analysis of both companies financial history, coupled with forecasted future performance and valuation as a means to infer on the potential synergetic effects that might arise from a merger. This is done by using methodologies that follow state of the art valuation approaches and are heavily supported by economic and financial theory, while still recognized by the top practitioners working in the areas of corporate finance and investment analysis. The outcome of this study has yielded mainly two conclusions: the fact that, by the end of 2010, both Hermès and LVMH’s stock seem to be overvalued by the market and that a merger would effectively give way to the creation of synergies, thus making it a sensible decision in economic and financial terms. In this sense, the share prices of LVMH and Hermès have been estimated at €118,83 and €126,26 per share, respectively, while the value of synergies was found to be approximately €10B.